Pelatihan Pengolahan Pupuk Organik Berbahan Limbah Buah Nanas Bernilai Ekonomis di Desa Babadan, Kec. Ngancar, Kab. Kediri - Maroeto, Maroeto; Priyadarshini, Rossyda; Winarno, Agung; Arum, Dewi Puspa; Santoso, Wahyu (Lembaga Dongan Dosen, 2024)
Babadan Village, Ngancar District, Kediri Regency is in an area close to Mount Kelud. This region has natural potential that supports agricultural activities so that the majority of people make their living as farmers. One of the main commodities grown is pineapple. Harvest results also leave waste that has not been processed and utilized optimally. Based on these problems, the East Java UPN Veteran Community Service Team initiated socialization activities and made organic fertilizer made from pineapple waste. The activity began with the delivery of material consisting of the benefits, disadvantages and advantages as well as marketing techniques for organic fertilizer. Next, activities were carried out to make organic fertilizer by combining materials from pineapple waste with other materials that have high nutrient content. Organic fertilizer is made through a fermentation process for 14 – 20 days. The results of laboratory analysis show that organic fertilizer contains the nutrients C - organic, N, P and K but in small quantities so that the use of organic fertilizer can be used in small-scale or home farming. There needs to be development and follow-up so that this organic fertilizer can be used in medium to large scale agriculture in the Kediri Regency area.